PEDAGOGICAL CONDITIONS FOR THE FORMATION OF VALEOLOGICAL CULTURE AMONG STUDENTS IN GRADES 5–9 IN THE GENERAL SECONDARY EDUCATION SYSTEM (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article examines the pedagogical conditions necessary for the formation of valeological culture among students in grades 5–9 within the general secondary education system. Valeological culture is interpreted as an integrative quality that combines knowledge about health preservation, motivation for a healthy lifestyle, responsible behavior, hygienic competence, physical activity habits, and a conscious attitude toward individual and social well-being. The study emphasizes that adolescence is a sensitive period for the development of health-related values, behavioral patterns, and self-regulation skills. Particular attention is given to the role of the school environment, interdisciplinary integration, age-appropriate instruction, teacher competence, family cooperation, and health-oriented extracurricular activities. The article argues that the effectiveness of valeological education depends on a systematic pedagogical approach that unites cognitive, emotional, motivational, and practical components. It is concluded that well-structured pedagogical conditions can significantly improve students’ health awareness, strengthen preventive behavior, and contribute to the sustainable development of a health-conscious generation.